The gypsies of early modern Spain, 1425-1783 - Pym, Richard J. (Palgrave Macmillan, 2007)
While a great deal has been written about Spain's minority populations of Jewish and Muslim origin in the late medieval and early modern periods, relatively little scholarly attention has been devoted to its gypsies. Drawing extensively on the author's archival research in Spain, The Gypsies of Early Modern Spain, 1425-1783 is the first major study in English of the first three-and-a-half centuries in Spain of a people, its gypsies or gitanos, who, despite their elevation by Spaniards and non-Spaniards alike to culturally iconic status in the nineteenth and twentieth centuries, have until now remained largely invisible to history in the English-speaking world. The book also offers insights into the nature and limits of royal power in early modern Spain, the Spanish Church and the Inquisition, and the complex larger society through which the gypsies moved.